High-strength lithium ion battery diaphragm and preparation method thereof
Patent Information
- Application Number
- CN202280099390.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2025-04-11
AI Technical Summary
Existing lithium-ion battery separators have difficulties in balancing mechanical strength and thermal dimensional stability, especially when they are thin and perform poorly at high temperatures.
By designing a core layer with a higher molecular weight and a surface layer with a lower molecular weight, combined with proportional control of the melt index of the polymer, a balance of low shrinkage and high strength of the separator is achieved, and specific preparation methods such as biaxial stretching and heat setting processes are used. Ensures high mechanical strength and thermal dimensional stability of the separator.
It achieves high mechanical strength and excellent thermal dimensional stability of the lithium-ion battery separator despite its thin thickness, as well as excellent breathability and puncture strength. It is suitable for power lithium-ion batteries with high energy density and high safety requirements.
Smart Images

Figure CN119816993A_ABST
Abstract
Description
A high-strength lithium-ion battery separator and preparation method thereof Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery separators, and in particular to a high-strength lithium-ion battery separator with thin thickness, high mechanical strength and excellent thermal dimensional stability, and a preparation method thereof. Background Art
[0002] In recent years, the popularity of new energy vehicles has rapidly increased, leading to increasingly stringent requirements for battery energy density and safety. While the separator, a key material in lithium-ion batteries, increases battery energy density through thinning and lightweighting, it must also possess sufficient mechanical strength to prevent breakage and short circuits caused by external forces during assembly and use. Furthermore, lithium-ion batteries often experience a certain degree of heat during manufacturing and the charging and discharging processes. If the separator has poor thermal dimensional stability, thermal deformation can directly lead to contact between the positive and negative electrode materials, resulting in a short circuit. Therefore, the thermal dimensional stability of the separator is a crucial safety indicator. However, thinner separators often experience a sharper drop in mechanical strength. Diaphragms with higher mechanical strength typically have poorer thermal dimensional stability.
[0003] Currently, the existing technology cannot provide a separator with both high mechanical strength and excellent thermal dimensional stability, especially a lithium-ion battery separator with a thin thickness, high mechanical strength and excellent thermal dimensional stability at high temperatures.
[0004] Summary of the Invention
[0005] The present invention addresses the technical difficulty of prior art in simultaneously maintaining both mechanical strength and thermal dimensional stability in lithium-ion battery separators, providing a lithium-ion battery separator with high mechanical strength and excellent thermal dimensional stability, and a method for preparing the same. In particular, the invention provides a lightweight, thin, and excellently mechanically strong and thermally stable battery separator.
[0006] Generally, the higher the mechanical strength of a polymer product, the worse its processability and thermal dimensional stability, and vice versa. To balance the mechanical strength and thermal dimensional stability of a polymer membrane, the present invention achieves a balance between low shrinkage and high strength by designing the membrane to include a higher molecular weight core layer and a lower molecular weight skin layer. The core layer has a high molecular weight, resulting in high shrinkage but high strength, while the skin layer has a low molecular weight, resulting in low shrinkage but low strength.
[0007] The present invention also found that since there is a certain correlation between the polymer melt index and the molecular weight of the polymer, by designing the diaphragm to include a core layer with a lower melt index and a surface layer with a higher melt index, it is possible to achieve a core layer with large shrinkage but high strength and a surface layer with small shrinkage but low strength, thereby achieving a balance between low shrinkage and high strength for the diaphragm.
[0008] Based on in-depth research on the membrane formulation, the present invention has also developed a method for preparing the membrane. This method ensures high mechanical strength without requiring a large stretch ratio, thereby facilitating the control of thermal dimensional stability and stretching uniformity. The method primarily comprises the following steps: melt-forming a surface layer material comprising at least a polyolefin and a pore-forming agent into a surface layer, and melt-forming a core layer material comprising at least a polyolefin and a pore-forming agent into a core layer; wherein the surface layer covers both the upper and lower surfaces of the core layer to form a laminate; biaxially stretching the laminate to obtain a stretched laminate; removing the pore-forming agent from the stretched laminate to obtain a membrane precursor; and heat-setting the membrane precursor to obtain the membrane.
[0009] Compared to conventional diaphragms, the diaphragm of the present invention significantly improves mechanical strength, particularly tensile strength, and exhibits excellent thermal dimensional stability at relatively high temperatures. Furthermore, the diaphragm of the present invention also exhibits excellent air permeability and puncture resistance. In particular, it achieves both high mechanical strength and excellent thermal dimensional stability even at relatively thin thicknesses.
[0010] In one embodiment, the present invention relates to a lithium ion battery separator, comprising a core layer and a surface layer covering the upper and lower surfaces of the core layer, wherein the core layer has porosity, the surface layer has porosity, and the surface layer and the core layer meet at least one of the following two conditions:
[0011] 1) The weight average molecular weight of the core layer polymer is 1.1 million to 1.7 million, for example, any one of 1.1 million, 1.15 million, 1.2 million, 1.3 million, 1.4 million, 1.45 million, 1.55 million, 1.6 million, and 1.7 million, or a range between any two thereof, preferably 1.2 million to 1.7 million, more preferably 1.3 million to 1.6 million, and further preferably 1.4 million to 1.55 million. The weight average molecular weight of the core layer polymer is 1.01 to 2.20 times the weight average molecular weight of the surface layer polymer, for example, any one of 1.01, 1.05, 1.09, 1.15, 1.30, 1.45, 1.60, 1.65, 1.75, 1.80, 2.10, and 2.20 times, or a range between any two thereof, preferably 1.05 to 1.80 times, and further preferably 1.10 to 1.30 times;
[0012] 2) The melt index of the surface layer polymer is 1.01-2.00 times, preferably 1.05-1.70 times, and more preferably 1.10-1.50 times the melt index of the core layer polymer. The measurement conditions of the melt index are 190°C and 2.16 kg / 10 min.
[0013] In the embodiment that meets condition 1), since the core and surface layers are both porous membrane layers and a specific core layer polymer is selected, the weight-average molecular weight of the surface layer polymer and the core layer polymer is controlled within a certain ratio range, so that the diaphragm has excellent air permeability while ensuring the mechanical strength of the diaphragm to a certain extent.
[0014] In the embodiment that meets condition 2), since the core surface layer is a porous membrane layer and the melt index of the surface layer polymer and the core layer polymer is set to a certain proportional relationship, the diaphragm has excellent air permeability while ensuring good mechanical strength and product processability.
[0015] In one embodiment, the present invention relates to a lithium-ion battery separator, wherein the porous membrane layer A polymer has a weight average molecular weight a or a melt index a', and the remaining central portion of the porous membrane layer B polymer has a weight average molecular weight b or a melt index b', which satisfies at least one of the following two conditions:
[0016] 1) The weight average molecular weight b is 1.1 million to 1.7 million, for example, any one of 1.1 million, 1.15 million, 1.2 million, 1.3 million, 1.4 million, 1.45 million, 1.55 million, 1.6 million, and 1.7 million, or any two thereof, preferably 1.2 million to 1.7 million, more preferably 1.3 million to 1.6 million, and further preferably 1.4 million to 1.55 million. The weight average molecular weight b is 1.01 to 2.20 times, preferably 1.05 to 1.80 times, and further preferably 1.10 to 1.30 times the weight average molecular weight a;
[0017] 2) The melt index a' is 1.01-2.00 times the melt index b', for example, it can be any one of 1.01, 1.05, 1.09, 1.15, 1.30, 1.45, 1.60, 1.65, 1.75, 1.80, 2.10, 2.20 times or a range between any two of them, preferably 1.05-1.70 times, more preferably 1.10-1.50 times. The melt index is measured at 190°C and 2.16 kg / 10 min.
[0018] In the embodiment that meets condition 1), since both membrane layer A and membrane layer B are porous membrane layers, and a specific porous membrane layer B polymer is selected, the weight-average molecular weight of the porous membrane layer A polymer and the porous membrane layer B polymer is controlled within a certain ratio range, so that the diaphragm has excellent air permeability while ensuring the mechanical strength of the diaphragm to a certain extent.
[0019] In the embodiment that meets condition 2), since both membrane layer A and membrane layer B are porous membrane layers, and the melt index of the porous membrane layer A polymer and the porous membrane layer B polymer are set to a certain proportional relationship, the diaphragm has excellent air permeability while ensuring good mechanical strength and product processability.
[0020] In a preferred embodiment, the core layer polymer or the porous membrane layer B polymer is a polyolefin, preferably a single type of polyethylene, or two or more polyethylenes, or a mixture of one or more polyethylenes and polypropylene; the surface layer polymer or the porous membrane layer A polymer is a polyolefin, preferably polyethylene, which is a single type of polyethylene, or a mixture of two or more polyethylenes; the weight-average molecular weight of the surface layer polymer or the porous membrane layer A polymer is 600,000-1.5 million, preferably 700,000-1.4 million, more preferably 900,000-1.4 million, and further preferably 1.1 million-1.35 million.
[0021] In a preferred embodiment, the surface layer or the porous membrane layer A comprises a first polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a second polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.3 million-1.8 million, and the weight ratio of the first polyethylene to the second polyethylene is 0-80:20-100, preferably 1-50:50-99, more preferably 0-40:60-100, and most preferably 15-35:65-85.
[0022] The core layer material or the porous membrane layer B material comprises a third polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a fourth polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.5 million-2 million, and the weight ratio of the third polyethylene to the fourth polyethylene is 0-30:70-100, preferably 1-10:90-99, more preferably 5-20:80-95,
[0023] The core layer or the porous membrane layer B optionally further comprises a fifth polypropylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and the fifth polypropylene accounts for 0-20% by weight of the core layer or the porous membrane layer B, preferably 0-13%.
[0024] In a preferred embodiment, the melt index of the surface layer polymer or the porous membrane layer A polymer is 0.35-0.7 g / 10 min, preferably 0.4-0.65 g / 10 min, more preferably 0.42-0.55 g / 10 min, and the melt index of the core layer polymer or the porous membrane layer B polymer is 0.3-0.6 g / 10 min, preferably 0.3-0.5 g / 10 min, more preferably 0.32-0.45 g / 10 min. The measurement conditions of the melt index are 190°C and 2.16 kg / 10 min.
[0025] In a preferred embodiment, the average pore size of the core layer or the porous membrane layer B is 30-50 nm, for example, any one of 30, 32, 35, 37, 40, 45, 50 nm, or a range between any two thereof, preferably 37-45 nm, and the average pore size of the surface layer or the porous membrane layer A is 35-60 nm, for example, any one of 35, 40, 45, 50, 55, 60 nm, or a range between any two thereof, preferably 40-50 nm. It will be understood that controlling the average pore size of the core surface layer or the porous membrane layer AB within a certain range is conducive to controlling a suitable air permeability, so that the diaphragm has good ion permeability.
[0026] In a preferred embodiment, the thickness of the diaphragm is 3-15 μm, preferably 10.5-11.5 μm, which further achieves the effect of thinning the diaphragm while ensuring air permeability.
[0027] In a preferred embodiment, the longitudinal heat shrinkage rate of the diaphragm at 120°C and 1h is less than 10%, preferably less than 6.5%, more preferably less than 6.0%, and most preferably less than 5.6%. The longitudinal heat shrinkage rate at 130°C and 30min is less than 17%, preferably less than 15%, preferably less than 14%, preferably less than 13%, more preferably less than 11.5%, and most preferably less than 10%. The transverse heat shrinkage rate of the diaphragm at 120°C and 1h is less than 10%, preferably less than 7%, more preferably less than 5.0%, and most preferably less than 4.0%. The transverse heat shrinkage rate at 130°C and 30min is less than 15%, more preferably less than 12.5%, more preferably less than 8.5%, and most preferably less than 6.5%. Preferably, the longitudinal (length direction) tensile strength of the diaphragm is ≥2980kgf / cm 2 , for example, it can be 2980, 3000, 3200, 3300, 3800, 4000, 4500, 5000, 6000, 6500, 7000 kgf / cm 2 Any one or the range between any two, preferably ≥3000kgf / cm 2 , more preferably 3300-6000kgf / cm2 The tensile strength of the diaphragm in the transverse direction (width direction) is ≥ 2980 kgf / cm 2 , for example, it can be 2980, 3000, 3200, 3300, 3800, 4000, 4500, 5000, 6000, 6500, 7000 kgf / cm 2 Any one or the range between any two, preferably ≥3000kgf / cm 2 , more preferably 3400-6000kgf / cm 2 .
[0028] In a preferred embodiment, the air permeability of the diaphragm is 50-250sec / 100ml, preferably 90-140sec / 100ml, the porosity of the diaphragm is 35-60%, preferably 40-48%, the puncture strength of the diaphragm is ≥200g, for example, it can be any one of 200, 400, 500, 550, 600, 650, 700, 800g or a range between any two of them, preferably ≥400g, more preferably 400-1500g, the sum of the thickness of the two surface layers or the sum of the thickness of the two porous membrane layers A is 5-20% of the thickness of the diaphragm, preferably 9-18%, and further preferably 12-15%, the weight average molecular weight of the diaphragm is 1.1 million to 1.6 million, preferably 1.2 million to 1.5 million, and further preferably 1.3 million to 1.45 million.
[0029] It is understood that when the thickness ratio of the surface layer or porous membrane layer A is higher, the heat shrinkage performance of the prepared membrane will be better, but the overall mechanical strength will be reduced. In this application, the thickness ratio of the surface layer or porous membrane layer A is controlled within a certain range, which is conducive to achieving appropriate heat shrinkage performance while pursuing high-strength membrane performance.
[0030] In one embodiment, the present invention relates to a method for manufacturing a lithium ion battery separator, comprising the following steps:
[0031] 1) Prepare the surface layer materials and core layer materials,
[0032] 2) melting and molding the surface layer material into a surface layer, and melting and molding the core layer material into a core layer, wherein the surface layer covers the upper and lower surfaces of the core layer to form a laminated body,
[0033] 3) biaxially stretching the laminate to obtain a stretched laminate,
[0034] 4) removing the pore former from the stretched laminate to obtain a separator precursor, and
[0035] 5) heat-setting the separator precursor to obtain the lithium-ion battery separator,
[0036] The surface layer material comprises a first polymer and a pore-forming agent, wherein the first polymer comprises a first polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a second polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.3 million-1.8 million, and the weight ratio of the first polyethylene to the second polyethylene is 0-80:20-100, preferably 1-50:50-99, more preferably 0-40:60-100, and most preferably 15-35:65-85.
[0037] The core layer material comprises a second polymer and a pore-forming agent, wherein the second polymer comprises a third polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a fourth polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.5 million-2 million, and the weight ratio of the third polyethylene to the fourth polyethylene is 0-30:70-100, preferably 1-10:90-99, and more preferably 5-20:80-95.
[0038] The second polymer optionally comprises a fifth polypropylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and the fifth polypropylene accounts for 0-20% by weight of the second polymer, preferably 0-13%.
[0039] In a preferred embodiment, the weight of the surface layer material accounts for 5-20% of the total weight of the surface layer material and the core layer material, preferably 9-18%, and further preferably 12-15%. In the surface layer material, the weight ratio of the first polymer to the pore former is 15-30:70-85, preferably 16-23:77-84, and / or, in the core layer material, the weight ratio of the second polymer to the pore former is 15-30:70-85, preferably 18-25:75-82.
[0040] In a preferred embodiment, before biaxially stretching the laminate, the laminate is cooled on both sides by passing it through a cooling bath, preferably a water bath, and the temperature of the cooling bath is 5-40°C, preferably 10-25°C, and more preferably 10-20°C. Double-sided cooling in a cooling bath allows for faster cooling of the laminate, more uniform cooling temperatures on its two opposing surfaces, more complete phase separation, and greater control over the performance consistency of the separator.
[0041] In a preferred embodiment, the biaxial stretching comprises:
[0042] 1) Longitudinal stretching: The laminate is longitudinally stretched at a temperature of 80-120°C, preferably 90-115°C, and a stretching ratio of 5.0-12.0 times, preferably 6.5-8.5 times.
[0043] 2) Transverse stretching: the laminate that has undergone the longitudinal stretching is subjected to transverse stretching at a temperature of 100-140° C., preferably 105-125° C., and a stretching ratio of 7.0-15.0 times, preferably 9.0-11.5 times.
[0044] In a preferred embodiment, the pore-forming agent is a small molecule solvent that can dissolve polyolefins, preferably liquid paraffin with a kinematic viscosity of 35 to 120 cps at 40°C.
[0045] In a preferred embodiment, the melt molding is carried out using multiple extruders, for example, three, preferably two extruders, one extruder (called the first extruder) is fed with the core layer material, and the other extruders (called the second extruders) are fed with the surface layer material, and then the laminate is formed through a co-extrusion die.
[0046] In a preferred embodiment, 1) the parameters of the second extruder include: extrusion temperature 150-250°C, screw speed 40-90r / min,
[0047] 2) The parameters of the first extruder include: extrusion temperature 150-250°C, screw speed 60-100r / min,
[0048] 3) The parameters of the co-extrusion die include: setting temperature 150-250°C.
[0049] In a preferred embodiment, the pore-forming agent is removed from the stretched laminate by using an extractant, wherein the extractant is an alkane extractant, preferably dichloromethane, and the extractant circulation feed volume is preferably 1 to 5 m 3 / h, and after extraction, the stretched laminate is optionally dried by heating it with one or more of a hot roller, a heating plate, and hot air, preferably at a drying temperature of 20 to 150°C.
[0050] In a preferred embodiment, the heat setting parameters include: a relaxation rate of 5-30% and a setting temperature of 120-145°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The present invention will be further described below with reference to the accompanying drawings.
[0052] FIG1 is a schematic diagram of the structure of a high-strength lithium-ion battery separator provided by the present invention.
[0053] In Figure 1: 1-upper surface layer; 2-core layer; 3-lower surface layer. DETAILED DESCRIPTION
[0054] Before further describing the present invention, the following sections collect certain terms used in the specification, examples, and appended claims. The definitions listed herein should be read and understood by those skilled in the art in light of the remainder of the present invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this invention belongs.
[0055] The terms “one” and “another” used herein are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the quantity of the indicated technical features.
[0056] As used herein, the term "about" when referring to a value is meant to encompass variations therefrom, such as ±10%, ±5%, ±1%, or ±0.1% of the particular value.
[0057] As used herein, the term "substantially the same" when referring to two values means that the two values differ by less than 10%, 5%, or 1% from the average of the two values.
[0058] As used herein, the term "polyolefin" may refer to a polyolefin monomer (ie, a single type of polyolefin), a polyolefin copolymer, or a polyolefin mixture.
[0059] Referring to Figure 1, the diaphragm of the present invention comprises a porous core layer 2 and porous surface layers covering the upper and lower surfaces of the core layer, namely the upper surface layer 1 and the lower surface layer 3 in Figure 1. In order to achieve a balance between low shrinkage and high strength for the diaphragm, the melt index or weight-average molecular weight of the surface layer polymer and the core layer polymer can be set to a specific ratio. The porous structure of the core layer and the surface layer also ensures the passage of ions in the electrolyte. In an optional embodiment, the melt index of the surface layer polymer is set to 1.01-2.00 times the melt index of the core layer polymer, preferably 1.05-1.70 times, and more preferably 1.10-1.50 times. In an optional embodiment, the weight average molecular weight of the core layer polymer can be 1.1 million to 1.7 million, preferably 1.2 million to 1.7 million, more preferably 1.3 million to 1.6 million, and further preferably 1.4 million to 1.55 million. The weight average molecular weight of the core layer polymer can be 1.01 to 2.20 times the weight average molecular weight of the surface layer polymer, preferably 1.05 to 1.80 times, and further preferably 1.10 to 1.30 times.
[0060] It is understood that the surface polymer and the core polymer described in the present application may be the same or different polymers, and different polymers refer to: polymers with different chemical properties (for example, a copolymer of PE and PP, which is a polymer with different chemical properties from a copolymer of PE and PE); and / or polymers with the same chemical properties but different characteristics (for example, two PEs with different characteristics (such as density, molecular weight, molecular weight distribution, rheology, additives (ingredients and / or percentages), etc.)). The types of polymers may be the same or completely consistent. The surface polymer and the core polymer may be independently selected polyolefins. The polyolefin may comprise an ethylene homopolymer, a propylene homopolymer, a copolymer of ethylene and propylene, or a mixture of the above polymers, for example, a single type of polyethylene, a mixture of two or more polyethylenes, or a mixture of one or more polyethylenes and polypropylenes. The polyolefin may be obtained by a one-step polymerization method or a multi-step polymerization method. Furthermore, in order to ensure processability, the melt index of the surface layer polymer used in the diaphragm of the present invention is 0.35-0.7g / 10min, preferably 0.4-0.65g / 10min, more preferably 0.42-0.55g / 10min, and the melt index of the core layer polymer is 0.3-0.6g / 10min, preferably 0.3-0.5g / 10min, more preferably 0.32-0.45g / 10min. The measurement conditions of the melt index are 190°C and 2.16kg / 10min.
[0061] The present invention controls the pore size of the membrane to be 30-60nm, the average pore size of the core layer to be 30-50nm, preferably 37-45nm, and the average pore size of the surface layer to be 35-60nm, preferably 40-50nm, to ensure good air permeability of the membrane.
[0062] The thickness of the diaphragm of the present invention is 3 μm or more, preferably 5 μm or more. In some possible embodiments, the thickness of the diaphragm can be 3 to 15 μm. It is understood that the thickness of the diaphragm can be any value such as 3 μm, 4.5 μm, 5 μm, 6 μm, 7.5 μm, 10 μm, 14.5 μm, 15 μm, or a range between any two values. For example, it is preferably 10.5 to 11.5 μm. The sum of the thicknesses of the two surface layers is 5-20% of the thickness of the diaphragm, preferably 9-18%, and more preferably 12-15%. The thicknesses of the two surface layers can be substantially the same or different, but preferably they are substantially the same.
[0063] Next, the preferred method for manufacturing the diaphragm of the present invention is discussed. However, as long as the resulting diaphragm has the characteristics that meet the requirements of the present invention, there are no restrictions on the polymer selection, pore-forming agent type, extrusion method, stretching method, extraction method, heat setting method, etc.
[0064] Specifically, the diaphragm of the present invention can be preferably obtained by the following preparation method:
[0065] 1. Raw Materials Preparation
[0066] The surface layer material and the core layer material are prepared separately. The surface layer material comprises a first polymer and a pore-forming agent, wherein the first polymer can be a polyolefin monomer or a polyolefin mixture. Preferably, the first polymer comprises a first polyethylene having a weight average molecular weight of 300,000-600,000 and a second polyethylene having a weight average molecular weight of 1.3 million-3 million. For example, the weight average molecular weight of the first polyethylene can be any value of 300,000, 350,000, 400,000, 450,000, 500,000, 550,000, or 600,000, or a range value between any two values, for example, preferably 400,000-550,000. For example, the weight average molecular weight of the second polyethylene can be any value of 1.3 million, 1.35 million, 1.4 million, 1.45 million, 1.5 million, 1.55 million, 1.6 million, 1.65 million, 1.7 million, or 1.8 million, or a range value between any two values, for example, preferably 1.3 million-1.8 million, and the weight ratio of the first polyethylene to the second polyethylene is 0-80:20-100, preferably 1-50:50-99, more preferably 0-40:60-100, and most preferably 15-35:65-85.
[0067] The core layer material includes a second polymer and a pore-forming agent. The second polymer can be a polyolefin monomer or a polyolefin mixture. Preferably, the second polymer includes a third polyethylene with a weight-average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a fourth polyethylene with a weight-average molecular weight of 1.3 million-3 million, preferably 1.5 million-2 million, and the weight ratio of the third polyethylene to the fourth polyethylene is 0-30:70-100, preferably 1-10:90-99, and more preferably 5-20:80-95. The second polymer optionally includes a fifth polypropylene with a weight-average molecular weight of 300,000-600,000, preferably 400,000-550,000, and the fifth polypropylene accounts for 0-20% by weight of the second polymer, preferably 0-13%.
[0068] The first polyethylene and the third polyethylene may be the same or different polyethylenes, and the second polyethylene and the fourth polyethylene may be the same or different polyethylenes.
[0069] Any pore-forming agent commonly used in the art can be used. For example, the pore-forming agent is a small molecule solvent that can dissolve polyolefins, preferably liquid paraffin with a kinematic viscosity of 35 to 120 cps at 40°C.
[0070] 2. Melt extrusion
[0071] Melt extrusion is performed using multiple, preferably two, extruders (e.g., twin-screw extruders). One extruder (referred to as the first extruder) is fed with the core layer material, while the remaining extruder (referred to as the second extruder) is fed with the surface layer material. The resulting polymer solution is sheared into a homogeneous polymer solution, which is then extruded through a three-layer die to form a laminate. Preferably, the barrels of both the second extruder and the first extruder are filled with nitrogen or other inert gas to prevent oxidative crosslinking reactions.
[0072] Preferably, the parameters of the second extruder include: extrusion temperature 150-250°C, screw speed 40-90r / min; the parameters of the first extruder include: extrusion temperature 150-250°C, screw speed 60-100r / min; the parameters of the co-extrusion die include: set temperature 150-250°C.
[0073] In other possible embodiments, the melt forming step may not utilize a co-extrusion die. For example, a layered lamination method may be employed, wherein sheets extruded from different dies are cooled, cast, stretched, extracted, dried, and heat-set separately before being laminated together. Alternatively, sheets extruded from different dies may be laminated together before subsequent stretching, extraction, heat-setting, and other steps. For specific process parameters, reference may be made to the process conditions for the various steps in this application.
[0074] In a possible embodiment, the weight of the surface layer material accounts for 5-20% of the total weight of the surface layer material and the core layer material, preferably 9-18%, and further preferably 12-15%. In the surface layer material, the weight ratio of the first polymer to the pore former is 15-30:70-85, preferably 16-23:77-84, and / or, in the core layer material, the weight ratio of the second polymer to the pore former is 15-30:70-85, preferably 18-25:75-82.
[0075] 3. Cooling the casting
[0076] The melt extruded from the die is attached to a cold roller to form a sheet. A water bath is used to accelerate the cooling rate of the sheet. The temperature of the cold roller is 10-40°C, and the water bath temperature is 10-40°C, preferably 10 to 25°C, and more preferably 10-20°C.
[0077] The casting process uses water bath cooling, which has the advantage of double-sided cooling compared to conventional single-roll cooling, resulting in good product performance consistency on both sides. Compared with the double-sided cooling method using two cold rollers, water bath cooling and film heat exchange time is longer, and cooling is more complete. In addition, due to the optimized formula and three-layer structure, a higher tensile strength can be achieved at a lower stretching ratio, thus preventing scratches on the film surface caused by stretching slip and uneven stretching caused by high stretching ratios. Currently known high-strength patents (for example: CN112592500A) have a longitudinal stretching ratio of approximately 15 to 20 times, and a transverse stretching ratio of approximately 11 to 20. In contrast, the longitudinal stretching ratio of the present invention is 5.0-12.0 times (preferably 6.5-8.5 times), and the transverse stretching ratio is 7.0-15.0 times (preferably 9.0-11.5 times). The tensile strength of the diaphragm is generally above 3000 (the existing technology is much lower than this value), and the thermal shrinkage at 120°C is less than 6% (the existing technology is generally above 10%).
[0078] 4. Stretch film
[0079] Longitudinal stretching: The sheet obtained from the casting is stretched along the machine direction (longitudinal direction) at a stretching temperature of 80 to 120°C and a stretching ratio of 5.0 to 12.0 times. It can be any value among 5 times, 5.5 times, 6 times, 6.5 times, 7 times, 7.5 times, 8.5 times, 10 times, 11 times, 12 times, or a range value between any two values, for example, preferably 6.5 to 8.5 times.
[0080] Transverse stretching: The thick sheet that has been longitudinally stretched is sent to a transverse stretching machine for transverse stretching. The stretching temperature is 100°C to 140°C, and the stretching ratio is 7.0 to 15.0 times. It can be any value among 7 times, 7.5 times, 8.5 times, 9 times, 10 times, 10.5 times, 11.5 times, 12 times, 13 times, 15 times, or a range value between any two values, for example, it is preferably 9.0 to 11.5 times.
[0081] 5. Extraction and drying
[0082] After stretching, the membrane is immersed in a tank containing an extractant, and the pore-forming agent is extracted using the principle of like dissolves like. The extractant is an alkane extractant, preferably dichloromethane, and the extractant circulation liquid flow rate is preferably 1 to 5 m 3 / h, and after extraction, the stretched laminate is optionally dried by one or more heating methods selected from the group consisting of a hot roller, a heating plate, and hot air, preferably at a drying temperature of 20 to 150°C, so that the residual extractant on the surface of the diaphragm is volatilized and can be recycled.
[0083] 6. Heat setting
[0084] The parameters of heat setting include: relaxation rate of 5-30% and setting temperature of 120-145° C. Under the same setting temperature, the greater the relaxation rate, the lower the thermal shrinkage of the diaphragm.
[0085] The present invention will be further explained below in conjunction with the examples. The following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0086] Example
[0087] Example 1
[0088] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0089] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0090] c) The polymer solutions in the second extruder and the first extruder were simultaneously injected into a 200°C three-layer co-extrusion die at a weight ratio of 13.9:86.1, wherein the surface layer polymer solution of the second extruder was distributed on both sides of the core layer polymer solution of the first extruder.
[0091] d) The melt (polymer solution) extruded through the die was cooled by a chill roll and a water bath to obtain a laminate having an ABA three-layer structure (ie, the structure shown in FIG1 ). The chill roll and the water bath were both at 25° C.
[0092] e) The laminate obtained in step d was longitudinally stretched at 103° C. and a magnification of 7.2; subsequently, it was transversely stretched at 117° C. and a magnification of 10.5.
[0093] f) The film obtained after biaxial stretching is immersed in an extraction tank filled with dichloromethane liquid, the liquid paraffin in the film is extracted, and then dried at 25-40°C.
[0094] g) The film obtained in step f is subjected to secondary stretching at 130° C. and a ratio of 1.4, and then heat-set at 134° C. and a relaxation rate of 18% to finally obtain a lithium-ion battery separator.
[0095] Example 2
[0096] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0097] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0098] c) The polymer solutions in the second extruder and the first extruder were simultaneously injected into a 200°C three-layer co-extrusion die at a weight ratio of 17.4:82.6, wherein the surface polymer solution of the second extruder was distributed on both sides of the core polymer solution of the first extruder.
[0099] d) Next, a lithium-ion battery separator was prepared according to steps d) to g) of Example 1.
[0100] Example 3
[0101] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0102] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0103] c) The polymer solutions in the second extruder and the first extruder were simultaneously injected into a 200°C three-layer co-extrusion die at a weight ratio of 10.4:89.6, wherein the surface polymer solution of the second extruder was distributed on both sides of the core polymer solution of the first extruder.
[0104] d) Next, a lithium-ion battery separator was prepared according to steps d) to g) of Example 1.
[0105] Example 4
[0106] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed in a weight ratio of 80:20 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added into a second extruder in a weight ratio of 18:82, melted and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0107] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0108] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0109] Example 5
[0110] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed in a weight ratio of 40:60 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added into a second extruder in a weight ratio of 18:82, melted and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0111] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed in a weight ratio of 30:70 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a first extruder in a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0112] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0113] Example 6
[0114] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0115] b) adding a fourth polyethylene powder (weight average molecular weight of 1.5 million) and liquid paraffin in a weight ratio of 18:82 into the first extruder, melting and mixing at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0116] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0117] Example 7
[0118] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0119] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 2,000,000) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0120] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0121] Example 8
[0122] a) a first polyethylene powder (weight-average molecular weight of 500,000) and a second polyethylene powder (weight-average molecular weight of 2,000,000) were measured and mixed at a weight ratio of 30:70 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0123] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 2,000,000) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0124] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0125] Example 9
[0126] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0127] b) a third polyethylene powder (weight average molecular weight of 500,000), a fifth polypropylene powder (weight average molecular weight of 500,000), and a fourth polyethylene powder (weight average molecular weight of 1.5 million) are measured and mixed in a weight ratio of 5:13:82 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin are added to a first extruder in a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0128] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0129] Example 10
[0130] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0131] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0132] c) The polymer solutions in the second extruder and the first extruder were simultaneously injected into a 200°C three-layer co-extrusion die at a weight ratio of 86.1:13.9, wherein the surface polymer solution of the second extruder was distributed on both sides of the core polymer solution of the first extruder.
[0133] d) Next, a lithium-ion battery separator was prepared according to steps d) to g) of Example 1.
[0134] Example 11
[0135] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0136] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 18:82 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0137] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0138] Example 12
[0139] a) a first polyethylene powder (weight average molecular weight of 500,000) and a second polyethylene powder (weight average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 20:80 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0140] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 5:95 to obtain a polyethylene mixture, and the polyethylene mixture and liquid paraffin were then added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0141] c) The polymer solutions in the second extruder and the first extruder were simultaneously injected into a 200°C three-layer co-extrusion die at a weight ratio of 78.3:21.7, wherein the surface layer polymer solution of the second extruder was distributed on both sides of the core layer polymer solution of the first extruder.
[0142] d) Next, a lithium-ion battery separator was prepared according to steps d) to g) of Example 1.
[0143] Comparative Example 1
[0144] a) a first polyethylene powder (weight-average molecular weight of 500,000) and a second polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 70:30 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0145] b) a third polyethylene powder (weight-average molecular weight of 500,000) and a fourth polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 50:50 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a first extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0146] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0147] Comparative Example 2
[0148] a) adding a second polyethylene powder (weight average molecular weight 1.3 million) and liquid paraffin in a weight ratio of 18:82 into a second extruder, melting and mixing at 200° C. and 80 rpm to obtain a surface polymer solution;
[0149] b) adding a fourth polyethylene powder (weight average molecular weight of 1.3 million) and liquid paraffin in a weight ratio of 18:82 into the first extruder, melting and mixing at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0150] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0151] Comparative Example 3
[0152] a) a first polyethylene powder (weight-average molecular weight of 500,000) and a second polyethylene powder (weight-average molecular weight of 1.5 million) were measured and mixed at a weight ratio of 70:30 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin were added to a second extruder at a weight ratio of 18:82, melted, and mixed at 200° C. and 80 rpm to obtain a surface polymer solution;
[0153] b) a third polyethylene powder (weight average molecular weight of 500,000), a fifth polypropylene powder (weight average molecular weight of 500,000), and a fourth polyethylene powder (weight average molecular weight of 1.5 million) are measured and mixed in a weight ratio of 30:20:50 to obtain a polyethylene mixture, and then the polyethylene mixture and liquid paraffin are added to a first extruder in a weight ratio of 18:82, melted, and mixed at 200° C. and 90 rpm to obtain a core layer polymer solution;
[0154] c) Next, a lithium-ion battery separator was prepared according to steps c) to g) of Example 1.
[0155] It can be understood that as long as the weight-average molecular weight or melt index of the membrane layer conforms to the gradient law defined in the present invention, the technical effect of the present invention can be achieved, and it is not limited to the ratio of the core-surface thickness. When there is a clear interlayer interface in the thickness direction of the membrane, the membrane layer at the interface toward the center of the membrane is the core layer, and the membrane layers on both sides of the membrane surface to the interface are the two side surface layers; or when the interlayer interface is not obvious, in a preferred embodiment, in the thickness direction of the membrane, 2.5-10%, preferably 4.5-9%, and more preferably 6-7.5% of the membrane layer thickness from the two side membrane surfaces toward the center of the membrane is the surface layer (single side) described in the present invention, and the remaining central part is the core layer.
[0156] The present invention uses the following test method for measurement.
[0157] thickness
[0158] The German Mahr C1208 thickness gauge was used for measurement according to GB / T6672-2001.
[0159] Air permeability
[0160] The measurement was performed using a Japanese Asahi EG01-55-1MR air permeability instrument according to GB / T 36363-2018.
[0161] Porosity
[0162] Measured using the mass method according to GB / T 36363-2018.
[0163] Puncture strength
[0164] The measurement was performed using a Chinese puncture test machine EM6.102 according to GB / T 36363-2018.
[0165] tensile strength
[0166] The measurements were performed using a Chinese tensile testing machine EM6.202 according to GB / T 1040[1].3-2006.
[0167] Thermal shrinkage
[0168] Mark and measure the distance L0 between two points on the diaphragm at room temperature (23°C), then place it between two A4 papers, and then put them together in a 120°C oven. Keep warm for 1 hour, then take them out and cool them naturally to room temperature (or put them together in a 130°C oven, keep warm for 0.5 hours, then take them out and cool them naturally to room temperature). Measure the distance L1 between the two points. The shrinkage rate = (L0-L1) / L0*100%.
[0169] Melt index
[0170] The measurements were performed using an MTS ZRZ1452 melt flow rate testing machine according to GB / T 3682.2-2018.
[0171] The compositions and property measurement data of Examples 1-12 and Comparative Examples 1-3 are shown in Table 1.
[0172] Table 1
[0173]
[0174]
[0175] Compared with the prior art, the present invention, through in-depth research on the ratio of the surface layer and core layer and the development of a supporting preparation process, produces a lithium-ion battery separator that combines the characteristics of lightness and thinness, high mechanical strength (especially tensile strength), and good thermal dimensional stability. It is particularly suitable for the field of power lithium-ion batteries with high energy density and high safety requirements. At the same time, the separator of the present invention has excellent air permeability and puncture strength. In addition, the preparation process disclosed in the present invention is simple, more suitable for high-speed, continuous production, and helps reduce the cost of the separator.
[0176] Furthermore, while ensuring excellent overall performance, the films of Examples 1-12 exhibited normal surfaces with no mottling. The films of Comparative Examples 1 and 2 exhibited normal surfaces, while the film of Comparative Example 2 exhibited slight mottling and processability issues. Examples 13, 14, 15, Comparative Examples 4, and 5 utilized the same raw material formulation as Example 1, differing only in the cooling method or stretch ratio. The measured property data are shown in Table 2.
[0177] Table 2
[0178]
[0179] The present invention notes that poor cooling of the casting will lead to uneven cooling, a mottled membrane surface, and poor performance consistency. Therefore, the present invention adopts a cooling bath to help the diaphragm cool quickly, making the phase separation in the wet film making process more complete. The preferred cooling time is more than 10s.
[0180] The present invention also notes that when the stretching ratio is too low, the molecular chain orientation is low, resulting in low product strength; when the stretching ratio is too high, the tensile stress is large, the thermal shrinkage is poor, and the diaphragm may even be directly broken.
[0181] The melt index of a polymer is related to its molecular weight. A melt index ratio of more than 2 for the skin layer to the core layer indicates a relatively low molecular weight in the skin layer, resulting in relatively low mechanical strength in the separator. A ratio equal to or less than 1 for the core layer fails to improve thermal shrinkage. By selecting an appropriate melt index ratio or weight-average molecular weight ratio, the present invention achieves a thinner separator with excellent strength and improved thermal shrinkage.
[0182] The present invention also noted that when the extrusion system temperature is too high, cross-linking reactions will occur between the raw materials, resulting in black spots. When the extrusion system temperature is low, the raw materials will not melt or the melting state will be poor, affecting production. When the extruder speed is too low, the raw material delivery efficiency is low and the pressure is unstable; when it is too high, the shear force is too strong, the molecular chain breaks, and the shear heat will also cause local cross-linking reactions in the polymer. The extraction liquid feed volume exceeds 5m 3 / h, it is easy to cause waste, and less than 1m 3 / h, the extraction is incomplete, affecting the overall performance of the membrane.
[0183] Preferably, the present invention obtains a diaphragm with excellent comprehensive performance by appropriately selecting various parameters.
[0184] In this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The methods described herein can be performed in any order that is logically possible, except for the specific order disclosed.
[0185] The representative examples are intended to help illustrate the present invention and are not intended to, and should not be construed as, limiting the scope of the present invention. Indeed, various modifications of the present invention and many other embodiments thereof, in addition to those shown and described herein, will become apparent to those skilled in the art, including the examples and the scientific and patent literature references cited herein. The examples contain important additional information, illustrations, and guidance that can be employed in the practice of the present invention in its various embodiments and equivalents.
Claims
1. A lithium ion battery separator, characterized in that The invention comprises a core layer and surface layers covering the upper and lower surfaces of the core layer, wherein the core layer is porous, the surface layer is porous, and the core layer and the surface layer meet at least one of the following two conditions: 1) The weight average molecular weight of the core layer polymer is 1.1 million to 1.7 million, preferably 1.2 million to 1.7 million, more preferably 1.3 million to 1.6 million, and further preferably 1.4 million to 1.55 million. The weight average molecular weight of the core layer polymer is 1.01 to 2.20 times, preferably 1.05 to 1.80 times, and further preferably 1.10 to 1.30 times the weight average molecular weight of the surface layer polymer; 2) The melt index of the surface layer polymer is 1.01-2.00 times, preferably 1.05-1.70 times, and more preferably 1.10-1.50 times, of the melt index of the core layer polymer. The melt index is measured at 190°C and 2.16 kg / 10 min.
2. A lithium ion battery separator, characterized in that: The polymer of the porous membrane layer A, which accounts for 2.5-10%, preferably 4.5-9%, and more preferably 6-7.5% of the membrane thickness from the two membrane surfaces toward the center of the membrane, has a weight average molecular weight a or a melt index a', and the polymer of the porous membrane layer B in the remaining central portion has a weight average molecular weight b or a melt index b', which satisfies at least one of the following two conditions: 1) The weight average molecular weight b is 1.1 million to 1.7 million, preferably 1.2 million to 1.7 million, more preferably 1.3 million to 1.6 million, and further preferably 1.4 million to 1.55 million. The weight average molecular weight b is 1.01 to 2.20 times the weight average molecular weight a, preferably 1.05 to 1.80 times, and further preferably 1.10 to 1.30 times; 2) The melt index a' is 1.01-2.00 times, preferably 1.05-1.70 times, and more preferably 1.10-1.50 times, of the melt index b'. The melt index is measured at 190°C and 2.16 kg / 10 min.
3. The lithium-ion battery separator according to claim 1 or 2, wherein the core layer polymer or the porous membrane layer B polymer is a polyolefin, preferably a single type of polyethylene, or a mixture of two or more polyethylenes, or one or more polyethylenes and polypropylene, the surface layer polymer or the porous membrane layer A polymer is a polyolefin, preferably polyethylene, which is a single type of polyethylene or a mixture of two or more polyethylenes, and the weight-average molecular weight of the surface layer polymer or the porous membrane layer A polymer is 600,000-1.5 million, preferably 700,000-1.4 million, more preferably 900,000-1.4 million, and further preferably 1.1 million-1.35 million.
4. The lithium ion battery separator according to claim 3, wherein the surface layer or the porous membrane layer A comprises a first polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a second polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.3 million-1.8 million, and the weight ratio of the first polyethylene to the second polyethylene is 0-80:20-100, preferably 1-50:50-99, more preferably 0-40:60-100, and most preferably 15-35:65-85. The core layer material or the porous membrane layer B material comprises a third polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a fourth polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.5 million-2 million, and the weight ratio of the third polyethylene to the fourth polyethylene is 0-30:70-100, preferably 1-10:90-99, more preferably 5-20:80-95, The core layer or the porous membrane layer B optionally further comprises a fifth polypropylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and the fifth polypropylene accounts for 0-20% by weight of the core layer or the porous membrane layer B, preferably 0-13%.
5. The lithium-ion battery separator according to any one of claims 1 to 4, wherein the melt index of the surface layer polymer or the porous membrane layer A polymer is 0.35-0.7 g / 10 min, preferably 0.4-0.65 g / 10 min, more preferably 0.42-0.55 g / 10 min, and the melt index of the core layer polymer or the porous membrane layer B polymer is 0.3-0.6 g / 10 min, preferably 0.3-0.5 g / 10 min, more preferably 0.32-0.45 g / 10 min, and the measurement conditions of the melt index are 190°C and 2.16 kg / 10 min.
6. The lithium ion battery separator according to any one of claims 1 to 5, wherein the average pore size of the core layer or the porous membrane layer B is 30-50 nm, preferably 37-45 nm, and the average pore size of the surface layer or the porous membrane layer A is 35-60 nm, preferably 40-50 nm. 7 . The lithium ion battery separator according to claim 1 , wherein the separator has a thickness of 3-15 μm, preferably 10.5-11.5 μm.
8. The lithium ion battery separator according to any one of claims 1 to 7, wherein the longitudinal thermal shrinkage of the separator at 120°C for 1 hour is less than 10%, preferably less than 6.5%, more preferably less than 6.0%, and most preferably less than 5.6%, and the longitudinal thermal shrinkage at 130°C for 30 minutes is less than 17%, preferably less than 15%, preferably less than 14%, preferably less than 13%, more preferably less than 11.5%, and most preferably less than 10%, and the transverse thermal shrinkage of the separator at 120°C for 1 hour is less than 10%, preferably less than 7%, more preferably less than 5.0%, and most preferably less than 4.0%, and the transverse thermal shrinkage at 130°C for 30 minutes is less than 15%, more preferably less than 12.5%, more preferably less than 8.5%, and most preferably less than 6.5%; Preferably, the longitudinal tensile strength of the diaphragm is ≥ 2980 kgf / cm 2 , preferably ≥3000kgf / cm 2 , more preferably 3300-6000kgf / cm 2 The tensile strength of the diaphragm in the transverse direction (width direction) is ≥ 2980 kgf / cm 2 , preferably ≥3000kgf / cm 2 , more preferably 3400-6000kgf / cm 2 .
9. The lithium ion battery separator according to any one of claims 1 to 8, wherein the air permeability of the separator is 50-250sec / 100ml, preferably 90-140sec / 100ml, the porosity of the separator is 35-60%, preferably 40-48%, the puncture strength of the separator is ≥200g, preferably ≥400g, more preferably 400-1500g, the sum of the thicknesses of the two surface layers or the sum of the thicknesses of the two porous membrane layers A is 5-20% of the thickness of the separator, preferably 9-18%, and further preferably 12-15%, and the weight average molecular weight of the separator is 1.1 million to 1.6 million, preferably 1.2 million to 1.5 million, and further preferably 1.3 million to 1.45 million.
10. A method for manufacturing a lithium-ion battery separator, characterized in that: The following steps are involved: 1) Prepare the surface layer materials and core layer materials, 2) melting and molding the surface layer material into a surface layer, and melting and molding the core layer material into a core layer, wherein the surface layer covers the upper and lower surfaces of the core layer to form a laminated body, 3) biaxially stretching the laminate to obtain a stretched laminate, 4) removing the pore former from the stretched laminate to obtain a separator precursor, and 5) heat-setting the separator precursor to obtain the lithium-ion battery separator, The surface layer material comprises a first polymer and a pore-forming agent, wherein the first polymer comprises a first polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a second polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.3 million-1.8 million, and the weight ratio of the first polyethylene to the second polyethylene is 0-80:20-100, preferably 1-50:50-99, more preferably 0-40:60-100, and most preferably 15-35:65-85. The core layer material comprises a second polymer and a pore-forming agent, wherein the second polymer comprises a third polyethylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and a fourth polyethylene having a weight average molecular weight of 1.3 million-3 million, preferably 1.5 million-2 million, and the weight ratio of the third polyethylene to the fourth polyethylene is 0-30:70-100, preferably 1-10:90-99, and more preferably 5-20:80-95. The second polymer optionally comprises a fifth polypropylene having a weight average molecular weight of 300,000-600,000, preferably 400,000-550,000, and the fifth polypropylene accounts for 0-20% by weight of the second polymer, preferably 0-13%.
11. The manufacturing method according to claim 10, wherein the weight of the surface layer material accounts for 5-20%, preferably 9-18%, and further preferably 12-15% of the total weight of the surface layer material and the core layer material, and in the surface layer material, the weight ratio of the first polymer to the pore former is 15-30:70-85, preferably 16-23:77-84, and / or, in the core layer material, the weight ratio of the second polymer to the pore former is 15-30:70-85, preferably 18-25:75-82.
12. The manufacturing method according to claim 10, wherein before biaxially stretching the laminate, the laminate is cooled on both sides by passing through a cooling bath, preferably a water bath, and the temperature of the cooling bath is 5-40°C, preferably 10 to 25°C, more preferably 10-20°C.
13. The manufacturing method according to claim 10, wherein the biaxial stretching comprises: 1) Longitudinal stretching: The laminate is longitudinally stretched at a temperature of 80-120°C, preferably 90-115°C, and a stretching ratio of 5.0-12.0 times, preferably 6.5-8.5 times. 2) Transverse stretching: the laminate that has undergone the longitudinal stretching is subjected to transverse stretching at a temperature of 100-140° C., preferably 105-125° C., and a stretching ratio of 7.0-15.0 times, preferably 9.0-11.5 times. The manufacturing method according to claim 11 , wherein the pore-forming agent is a small molecule solvent that can dissolve polyolefin, preferably liquid paraffin with a kinematic viscosity of 35 to 120 cps at 40° C.
15. The manufacturing method according to any one of claims 10 to 14, wherein the melt molding is carried out using multiple, preferably two, extruders, one extruder (called the first extruder) is fed with core layer materials, and the remaining extruders (called the second extruders) are fed with surface layer materials, and then the laminate is formed through a co-extrusion die.
16. The manufacturing method according to claim 15, wherein: 1) The parameters of the second extruder include: extrusion temperature 150-250°C, screw speed 40-90r / min, 2) The parameters of the first extruder include: extrusion temperature 150-250°C, screw speed 60-100 r / min, 3) The parameters of the co-extrusion die include: setting temperature 150-250°C.
17. The manufacturing method according to any one of claims 10 to 16, wherein the pore-forming agent is removed from the stretched laminate by using an extractant, wherein the extractant is an alkane extractant, preferably dichloromethane, and the extractant circulation feed volume is preferably 1 to 5 m 3 / h, and after extraction, the stretched laminate is optionally dried by heating it with one or more of a hot roller, a heating plate, and hot air, preferably at a drying temperature of 20 to 150°C.
18. The manufacturing method according to any one of claims 10 to 17, wherein the parameters of the heat setting include: The relaxation rate is 5-30% and the setting temperature is 120-145℃.